Analysis study of New Business Models (Insurance Technology) in Indonesia - Prihanto, Agung (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
With the COVID-19 pandemic in Indonesia, several insurance companies need a sales strategy for marketing their products. Especially in health insurance products, in addition to health insurance, which has become a trend that is needed by the community, the global epidemic makes people safer if they have health insurance. Digital channels are indeed an opportunity for insurance marketing during the pandemic, although the portion is still small compared to agencies, banks, and telemarketing. Based on OJK data, the total premium recorded by the insurtech platform during 2020 reached Rp. 811.7 billion. AAJI noted that the premium from digital distribution channels in 2019 only reached Rp. 13.6 billion. This figure will more than double in 2020 to IDR 31.5 billion. In terms of its contribution to the total premiums of the life insurance industry, the portion is still very small, which is still below 0.1 percent. The new business model in insurtech has not been able to contribute to profits for insurance companies in general. This is due to many factors that influence it.